Analysis of the Pop Up Market in Islamic Economics Business Perspective: Lesson Learned in Pekanbaru - Nurhadi Nurhadi (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2019)
The market phenomenon in Pekanbaru in the last decade is enlivened by the existence of the pop-up market. By utilizing idle land around the settlement, the sellers provide goods for daily needs. This study is a mixed research model, which uses qualitative descriptive methods and direct observation. The research shows that the pop-up market just a momentary event that occurs when there is a crowd. It can be categorized as a traditional market with basic goods and carried out on mobile. According to a business economics perspective, the pop-up market plays an important role in fostering economic development, which leads to the welfare of society. Further, the existence of the pop-up market also in accordance with the principles of Islamic business economics which give attention to the micro and small enterprises due to the target of the pop-up market in Pekanbaru is the middle and lower classes. Keywords: Islamic Economics, Islamic Business, Pop Up Market